High-risk JAK2 V617F allele burden in a five-year cohort of myeloproliferative neoplasm patients - Chatambudza, Moses (My University, 2019)
Introduction JAK2 V617F is the most common somatic mutation associated with essential thrombocythemia (ET), polycythaemia vera (PV) and primary myelofibrosis (PMF). JAK2 V617F allele burden is important for diagnosis, prognosis and disease monitoring. This study aimed to verify detection and quantitation of allele burden using a commercial quantitative allele specific PCR assay (QUASA). Furthermore, the study intended to determine JAK2 V617F allele burden in a five-year retrospective cohort of patients previously diagnosed with ET, PV and PMF. Materials and Method QUASA was verified using World Health Organization (WHO) DNA standards, external quality assurance material (EQA) and characterised remnant patient DNA samples. A laboratory database search was performed to identify demographic and laboratory results of all patients who tested positive for JAK2 V617F mutation in the Molecular and Virology Laboratory at Charlotte Maxeke Johannesburg Academic Hospital from 1 January 2012 to 31 December 2016. Allele burden was measured on residual DNA samples from these patients that were previously diagnosed with JAK2 V617F-positive ET, PV and PMF. Results QUASA correctly detected JAK2 V617F mutation qualitatively in all samples tested (WHO standards, EQA material and remnant patient DNA samples). It quantified the allele burden from 0,1% to 100% with a bias of 0,288 and correlation coefficient of 0,9999. One thousand two hundred and twenty (1220) screens were performed for JAK2 V617F mutation over the 5year period. Of these, 205 were found to be positive. Median age at diagnosis of myeloproliferative neoplasms (MPNs) was 65 years with a male: female ratio of 1,1:1. ET, PV and PMF accounted for 11%, 46% and 43% of the MPNs, respectively. Median allele burden for ET, PV and PMF was 47,25%, 72,05% and 62,62%, respectively. Allele burden was significantly lower in ET compared to PV (p=0,011) and PMF (p=0,025) and correlated with leucocytosis, neutrophilia, eosinophilia and a low erythrocyte mean cell volume (p<0,05). Conclusion QUASA is sensitive and specific for detecting JAK2 V617F, as well as accurate and precise in quantitating allele burden. JAK2 V617F-positive MPNs occurred in older patients with approximately equal sex ratio. ET was the least common MPN. Allele burden was overall high for all 3 subtypes of MPNs, which may predispose to a poorer prognosis. A prospective community-based study would be invaluable to confirm the above findings and to establish an accurate database of MPNs in South Africa. Prospective follow-up of a cohort of patients with known allele burden and correlation with clinical outcome would also be of great value.
A research report submitted as a “submissible article” to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine (Haematology) Johannesburg, 2019